The effect of host condition on adult emerald ash borer (Agrilus planipennis) performance. (10th April 2019) - MacQuarrie, Chris J K
Abstract: For invasive species, how successful adult insects are in various life history processes influences how well invaders can colonize and reproduce. Emerald ash borer (EAB) is a significant invasive forest insect in North America that has killed millions of ash trees. While the effect of host condition on larval performance has been examined, the effect of host condition on adult performance has not. In this study, healthy trees were girdled to simulate poor host condition and then both artificially and naturally infested by EAB. The ensuing adults that developed and emerged were then assessed for their success in terms of number, lifespan, size, mating success and fecundity. Girdling reduced the number of insects that emerged from trees, and was associated with reduced lifespan, but had confounding effects on mating success and fecundity. Adult size was positively affected by girdling but negatively affected by crowding that larvae experienced during development. This suggests that it is not necessary to consider host condition when assessing the risk of EAB, as the dynamics of populations attacking poor-condition trees will be the same as the dynamics populations attacking healthy trees.